Wacana Radikalisme di Universitas Islam Negeri (UIN) Alauddin Makassar; Kontestasi dan Pertarungan Gagasan di Ruang Publik Kampus - Muqsith, Awal (FIKRAH, 2022)
This article discusses of circulation processes and dissemination of radicalism ideas at the Alauddin State Islamic University (UIN) Makassar. Thisarticle uses a qualitative research method that seeks to interpret and describe patterns of radicalism infiltration strategies. In order to achieve that goals, the study used survey that has been followed by three hundred and fifty respondents from all faculty of Alauddin State Islamic University (UIN) which took place from January to May 2019. The survey used questioner with multiple choice questions pattern. The results showed that there was a split view and contesting concept among students between accepting Pancasila and the idea of the Islamic state. The very sensitive political issues of political Islam circulated inadequately in UIN Alauddin Makassar. Therefore, the radical ideas will easily infiltrate the minds of students using lip service and manipulation of sensitive Islamic political teachings. The Campus mosque is the most vulnerable area to be used as a platform for spreading radical ideas. The radical forum is usually camouflaged in an ordinary-teaching form, which makes it difficult for students to identify. The case that occurred in UIN Alauddin Makassar could be occurred in other Islamic universities and colleges in Indonesia.